If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 + x = -27 Solving -15 + x = -27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + x = -27 + 15 Combine like terms: -15 + 15 = 0 0 + x = -27 + 15 x = -27 + 15 Combine like terms: -27 + 15 = -12 x = -12 Simplifying x = -12
| 5*18+9y=45 | | 3x^2=-8x+128 | | 6x^2-x-36=0 | | 2.33+3.33y=3y-4 | | -300=-15k | | -5(1-3r)=28+4r | | 5+2x=4x-13 | | 4n+6+-2n=2(n+3) | | 5x+9*0=45 | | 1+6.33z=-2.5 | | 0.062=-0.06m-0.01 | | x^2-20=-125 | | 85=-5(2r-7) | | 4(3-2n)=n+66 | | -4m-7(6-2m)=22 | | 5*0+9y=45 | | .33x=1.33 | | 8y-12-4y+9=0 | | 8y+7=4y-29 | | 9(4-2x)=3(2-6x) | | 15x^2-50x=0 | | 5x-4x=-6+3 | | 0.60x+0.30(70)=0.30(148) | | h/3+h/6=1 | | 7y-20=-2y-47 | | 9=-4.3 | | -6+6n=6(10-10n) | | 3m+8=m+18 | | 36p+4j=33 | | 3x^4+21x^3-36x^2+3=0 | | 2g+4h=47 | | 2g*4h=47 |